Genuine French WWII M-209 cryptograms. Issue 5 (3rd September 2019) - Bouchaudy, Jean-François
Abstract: In the French Army archives three cryptograms encrypted by the M-209 were found. They date from 1944 and come from the 1st French Army. Since the security rules in the military require them to be destroyed, it is extremely rare to have access to this type of document. This article aims to show the use of the M-209 in the French Army. It will first briefly describe the operation of the M-209 encryption machine and describe the cryptographic means used by the French Army during the Second World War, including the M-209 provided by the Americans. The three cryptograms found in the archives will then be studied. The various components of these messages are described, starting with the key groups (which provide the message key) and continuing to the main abbreviations as well as some codenames. The plaintexts will then become understandable. This article ends with the reconstruction of the keys (internal and external) of the first two messages. This reconstruction could not be completed for the third message: it is given as a challenge to the readers of Cryptologia . This is also the opportunity to balance the security of the M-209 with that of the Enigma.